PERANAN BADAN PERMUSYAWARATAN DESA (BPD) DALAM PEMBANGUNAN DESA DI KECAMATAN BADIRI KABUPATEN TAPANULI TENGAH* - Rahman Husein Siregar (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2019)
The research strives for analyzing the roles of Village Representative Council (BPD) in Village Development at Kecamatan Badiri Kabupaten Tapanuli Tengah. It also tries to identify hindrances and efforts conducted to overcome the hindrances in the village development. The first variable, the roles of Village Representative Council (BPD), consists of two sub-variables, i.e.: village regulationmaking and the accommodation of community aspiration. The second variable, village development, comprises three variables, i.e.: living standard improvement, community participation in development, and community capacity to be self-reliant.The research result reveals that the roles of Village Representative Council (BPD) as the media and mechanism for village development are moderately good but need to be optimized through the socialization of or information distribution regarding village development to the community.